Biological investigation of N-methyl thiosemicarbazones as antimicrobial agents and bacterial carbonic anhydrases inhibitors. (31st December 2022) - D'Agostino, Ilaria; Mathew, Githa Elizabeth; Angelini, Paola; Venanzoni, Roberto; Angeles Flores, Giancarlo; Angeli, Andrea; Carradori, Simone; Marinacci, Beatrice; Menghini, Luigi; Abdelgawad, Mohamed A.; Ghoneim, Mohammed M.; Mathew, Bijo; et al.
Abstract: The enormous burden of the COVID-19 pandemic in economic and healthcare terms has cast a shadow on the serious threat of antimicrobial resistance, increasing the inappropriate use of antibiotics and shifting the focus of drug discovery programmes from antibacterial and antifungal fields. Thus, there is a pressing need for new antimicrobials involving innovative modes of action (MoAs) to avoid cross-resistance rise. Thiosemicarbazones (TSCs) stand out due to their easy preparation and polypharmacological application, also in infectious diseases. Recently, we reported a small library of TSCs (1–9 ) that emerged for their non-cytotoxic behaviour. Inspired by their multifaceted activity, we investigated the antibacterial, antifungal, and antidermatophytal profiles of derivatives 1–9, highlighting a new promising research line. Furthermore, the ability of these compounds to inhibit selected microbial and human carbonic anhydrases (CAs) was assessed, revealing their possible involvement in the MoA and a good selectivity index for some derivatives. Graphical Abstract: UF0001